CRITERIA, INDICATORS AND LEVELS OF HEALTH-PRESERVING COMPETENCE FORMATION IN JUNIOR SCHOOLCHILDREN - Лоюк, Оксана (SWorldJournal, 2024)
The article proves the relevance and necessity of forming the junior schoolchildren’s health-preserving competence. The essence of the concept of "junior schoolchildren’s health-preserving competence" has been determined based on the disclosure of the ess